Analysis Of Overall Equipment Effectiveness (Oee) And Determining Six Big Losses To Increase The Effectiveness Of Lb 02 Lath - Helena Sitorus; Zulkani Sinaga; Syaiful Islam (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2022)
Breakdown is one of the problems faced by the manufacturing company PT. Bakrie Autoparts which is engaged in the Disc Brake automotive component industry for four or more wheeled vehicles. There was a breakdown on the LB 02 lathe an average of 42.5 hours per month that exceeded the tolerance limit determined by the company which is 25 hours per mont causing the production target not to be achieved. Based on this, research is carried out which aims to calculate the Overall Equipment Effectiveness (OEE) value, determine the most dominant type of Six Big Losses, and provide suggestions for improvement efforts to increase the effectiveness of the LB 02 lathe. The results showed the average value of Overall Equipment Effectiveness ( OEE) lathe LB 02, which is 81.43%, then this value is included in the moderate condition which includes an availability rate of 86.80%, a performance rate of 94.15%, a quality rate of 99.70%. Equipment Failure Losss is the most dominant in influencing the decrease in the effectiveness of the LB 02 lathe with an average value of 8.40% with an influence percentage of 46.41%. Proposed improvements include checking the source and supply voltage every day before starting the production process, checking and replacing engine parts, especially belts once a week and every 3 months for replacement, and checking the condition of lubricating oil and coolant every day after the production process. Keywords: Overall Equipment Effectiveness (OEE), Six Big Losses, Breakdown.